Migration practitioners' roles in communicating credible refugee claims. (June 2020) - Smith-Khan, Laura
This article explores the important communicative roles that Australian migration lawyers and agents play when assisting refugee visa applicants, with particular attention to how they contribute to the (re)construction of applicant credibility. It identifies a range of communicative choices and concludes that practitioners have a variety of individual beliefs and skills that lead them to participate in applications and appeals in diverse ways. This indicates the potential for diverse experiences and outcomes for individual asylum seekers based on the assistance they have.